2019
DOI: 10.1097/md.0000000000014165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mitochondrial ATP-sensitive potassium channel activation (nicorandil) in patients with angina pectoris undergoing elective percutaneous coronary interventions

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Clinically, nicorandil is applied as a treatment of chronic stable angina in patients with effort-induced symptoms arising from epicardial coronary artery stenoses, coronary vasospasm and microvascular dysfunction 10. A few clinical trials have indicated that nicorandil is effective to reduce the frequency of angina episodes and improve exercise capacity in patients with stable angina 11. Moreover, nicorandil is well tolerated by most patients, with a satisfactory safety profile as evidenced by accumulating studies 12.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, nicorandil is applied as a treatment of chronic stable angina in patients with effort-induced symptoms arising from epicardial coronary artery stenoses, coronary vasospasm and microvascular dysfunction 10. A few clinical trials have indicated that nicorandil is effective to reduce the frequency of angina episodes and improve exercise capacity in patients with stable angina 11. Moreover, nicorandil is well tolerated by most patients, with a satisfactory safety profile as evidenced by accumulating studies 12.…”
Section: Introductionmentioning
confidence: 99%
“…This was partly consistent with the results of previous studies, which claimed that nicorandil had a negative effect on PMI. [ 34 38 ] Note that a moderate decrease in the incidence of PMI was detected after the intracoronary administration of nicorandil and alprostadil via a targeted perfusion microcatheter, which differed sharply in the way of drug administration from those studies. Since this trial was not primarily designed to determine the comparative efficacy of these drugs on PMI, future studies are encouraged to elucidate the cardiac protective effect of intracoronary nicorandil and alprostadil from this perspective.…”
Section: Discussionmentioning
confidence: 95%
“…The study by Zhang et al [ 36 ] suggested that nicorandil, as an adjuvant therapy with PCI, can reduce total mortality and cardiovascular death in patients with primary PCI (PPCI) and elective PCI (EPCI) and reduce heart failure in PPCI patients. Zhu et al [ 37 ] said that nicorandil did not reduce the overall incidence of perioperative complications and the incidence of major adverse cardiac events (MACE) in patients with angina pectoris who underwent elective PCI. Li et al [ 38 ] suggested that nicorandil could improve clinical outcomes in terms of perioperative myocardial infarction (MI).…”
Section: Discussionmentioning
confidence: 99%